Digital climate advisories aid 5,000 monsoon rice farmers in Myanmar - Swaans, Cornelis; Khaung, Ye (2024)
In 2023, 5,000 rice-growing smallholder farmers from five townships in the Irrawaddy Delta used agroclimatic advisories in their planning and decision-making to reduce climate risks. In partnership with Village Link Company Ltd., DeRisk SE Asia and the CGIAR research initiative Asian Mega-Deltas initiated the pilot provision of climate advisories for monsoon rice farmers. The advisories were developed based on monthly and weekly weather forecasts following Crop Decision Trees for different climate scenarios.